Analisis Yuridis Dugaan Kartel Bunga Pinjaman Daring serta Implikasinya Terhadap Perlindungan Konsumen (CV. Era Digital Nusantara, 2025)
The rapid growth of Information Technology-Based Co-Funding Services (LPBBTI) in Indonesia presents significant regulatory challenges, particularly concerning interest rate determination. This study examines the alleged online lending interest rate cartel involving the Indonesian Joint Funding Fintech Association (AFPI) and its implications for consumer protection. Employing normative juridical research with a statutory approach, this research evaluates AFPI's legal standing in establishing interest rate caps during 2018 and 2021. Findings indicate that under OJK Regulation Number 77 of 2016, AFPI lacked the authority as a Self-Regulatory Organization (SRO) to independently mandate interest rates. Such collective action potentially violates Law Number 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition by fulfilling the elements of price-fixing among competitors. The regulatory void prior to OJK Circular Letter Number 19 of 2023 created legal uncertainty detrimental to consumers. Therefore, proactive regulatory intervention remains essential to establish fair economic benefit caps today.